A literature review of Islamic transactions profit - Nadhirah, Gazali; Nurfadhlina, Abdul Halim; Puspa Liza, Ghazali; Salman, Lambak; Hazimi, Mohd Foziah; Juliana, Arifin; Ahmad Shukri, Yazid; Eni Noreni, Mohamad Zain; Abdul Talib, Bon (2020)
This paper presents views on profit from Islamic perspective. The profit is one of the aims of the transaction such as loan, hire-purchase and purchase. However, the determination of the profit rate in Islam has boundaries. There are three main point has been discussed in this paper such as profit maximization in Islam, profit rate which prohibited in Islam and the determination of the profit. This paper reviews the way to acquire profit that follows Shariah compliance.